Layout Design of Work Facilities in the Home Industry of the Papuan Community, Wania District - Rasul, A.; Sonda, Ruben; Nudin, Subha (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
One of the efforts offered is Designing the Layout of Work Facilities in the Home Industry of the Papuan Community, Wania District. Designing the Layout of Work Facilities in Irul's Home Industry by making spoons from coconut shells and wood. The aim of this service is to increase the potential of a wide open market, a selling price that is able to compete with other craftsmen. So the problem that occurs in this home industry is the lack of conventional equipment used, in the form of drills, saws, planers and sandpaper. The layout of the production room facilities is still not organized, so the production flow is still less effective and efficient. in the production process. Apart from that, the livestock pen, cooking area and production area are still one space without partitions, so it gives the impression of being untidy, so it takes a lot of time to sand the coconut shells. Sanding was carried out three times, starting with coarse, medium and fine sandpaper. This product is marketed by selling it in traditional markets in the Secang area and in several areas outside the city. The methods used to solve this problem are: counseling, training and mentoring. The results achieved in this activity are that the equipment becomes more modern, gets a bigger market, a better layout to support the production process and the amount of production can increase. The waste produced has economic value and is sold to oyster mushroom entrepreneurs as a planting medium, so that the products produced will increase compared to before.